Corn vs. sorghum grain for growing-finishing pigs - Koch, B.A.; Cowman, G.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Kansas swine growers are quite sure' that corn-fed growing-finishing pigs will outperform those fed sorghum grain. Just as many others feel that sorghum grain is equal to corn in swine rations. Most of the time sorghum grain is lower in price per pound than corn. Research results suggest that corn and sorghum grain are quite similar in chemical composition and in feeding value. Sorghum grain is more variable in crude protein content than corn. One recent comparison between corn and sorghum grain is summarized in this report.
Swine Industry Day 1968 is known as Swine Day, 1968
Keywords: Swine; Corn vs. sorghum grain; Growing-finishing pigs